Head mounted displays for capturing head kinematics in postural tasks - Lubetzky, A. V.; Wang, Z.; Krasovsky, T. (Journal of Biomechanics, 2019)
Tracking head motion in a simple, portable and accurate manner during performance of postural tasks in a virtual reality environment could have important implications for investigating normal and pathological head kinematics. We investigated concurrent validity of head tracking of two Head Mounted Displays (HMDs), Oculus Rift and HTC Vive, vs. a gold-standard motion capture system (Qualisys). Head kinematics of N = 20 healthy young adults was quantified during static and dynamic postural tasks. While wearing the Oculus Rift or HTC Vive, participants observed moving stars (static tasks) or a flying ball (dynamic task). Head kinematics were recorded simultaneously by the Rift or Vive and Qualisys camera system. We calculated head directional path, acceleration in 6 directions and volume of translation movement. Intra-Class Correlations (ICC) and 95% Limits of agreement were calculated. Most ICC values were around 0.9 with several at 0.99 indicating excellent agreement between the HMDs and Qualisys. Weaker agreement was observed for vertical displacement during a static task and moderate agreement was observed pitch and yaw displacement during a dynamic task. A negative bias of a small magnitude (indicating more movement in VR) was observed for most variables in static tasks, while a positive bias was observed for most variables in the dynamic task (indicating less movement in VR). Our results generally support the concurrent validity of Oculus Rift and HTC Vive head tracking during static and dynamic standing tasks in healthy young adults. Specific task- and direction-dependent differences should be considered when planning measurement studies using these novel tools.